2017
DOI: 10.3238/arztebl.2017.0141
|View full text |Cite
|
Sign up to set email alerts
|

ADHD in Germany: Trends in Diagnosis and Pharmacotherapy

Abstract: The administrative prevalence of a diagnosis of ADHD among adults and the degree of medication use for ADHD by adults have risen in recent years. This can be interpreted as an indication of the sensitization of physicians and patients to the possibility of adult ADHD. Nonetheless, the prevalence of diagnosed ADHD remains less than the prevalence revealed by epidemiologic studies. This may indicate that adults with ADHD are currently underdiagnosed and undertreated. The low rate of use of ADHD medications among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 49 publications
(42 reference statements)
7
43
0
5
Order By: Relevance
“…A few studies reported about rising trends of disease frequency (reviewed in 6 ). In Germany, an increase in prevalence was reported by two studies 3,7 ; e.g . from 2.5% in 2005 to 4.2% in 2015 3 and from 5.0% in 2009 to 6.1% in 2014 7 , although some studies showed no increase in recent years.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A few studies reported about rising trends of disease frequency (reviewed in 6 ). In Germany, an increase in prevalence was reported by two studies 3,7 ; e.g . from 2.5% in 2005 to 4.2% in 2015 3 and from 5.0% in 2009 to 6.1% in 2014 7 , although some studies showed no increase in recent years.…”
Section: Introductionmentioning
confidence: 89%
“…In Germany, an increase in prevalence was reported by two studies 3,7 ; e.g . from 2.5% in 2005 to 4.2% in 2015 3 and from 5.0% in 2009 to 6.1% in 2014 7 , although some studies showed no increase in recent years. The question arising in this context is whether the prevalence increase over the last years is true or whether it is just the result of the heightened attention from the public, media and scientific community.…”
Section: Introductionmentioning
confidence: 89%
“…Prevalence rates in children and adolescents represent averaged values across the full age range, but peak prevalence may be much higher in certain age groups, for example, 13% in 9-year-old boys. 35 Universal ADHD prevalence in adults is estimated to lie at 2.8%, with higher rates in high-income (3.6%) than in low-income (1.4%) countries. 36 True prevalence rates (also called community prevalence, e.g., Sayal et al 37 ) should be based on population-based representative health surveys, that is, the actual base rate of ADHD in the population, in contrast to the administrative base rate, which is related to clinical data collection (Taylor 38 ).…”
Section: Definitions and Phenomenologymentioning
confidence: 99%
“…ADHD diagnoses were identified by the ICD-10 codes F90.0, F90.1, F90.8, F90.9, or F98.8 from the baseline period. These ICD-10 codes were used in a recent study to identify ADHD patients in German health insurance data (Bachmann et al 2017). Individuals with an atomoxetine (ATX) prescription prior to the initial MPH prescription or with prescriptions of lisdexamfetamine (LIS) or dexamfetamine (DEX) at any time were excluded since these drugs played a minor role in clinical practice during the study period.…”
Section: Cohort Definitionmentioning
confidence: 99%